Funding Continuum for Private Business Owners: Evidence from the Pepperdine Private Capital Markets Project Survey - Maretno A. Harjoto; John K. Paglia (The Journal of Entrepreneurial Finance (JEF), 2011)
The Pepperdine Private Capital Markets Project survey for business owners, administered during the spring of 2010, reveals an increasingly important role of friends and family (Friends/Family) to provide capital for privately-held businesses. Examining business owners perceptions of their sources of capital reveals that, overall, business owners prefer Friends/Family and angel financing as well as asset-based lenders and banks (ABL/Bank). Business owners consider Friends/Family financing to be the least costly. However, business owners also believe venture capital (VC), private equity (PE), and angels provide more benefits than friends/family and ABL/Bank. This study unveils a detailed spectrum of the funding continuum for privately owned firms across different levels of firms size, age, and information availability.
Keywords: G10; G20; G24; G31; 650; Funding continuum; private capital markets; business owners impressions